The Reason for the Insufficient Development of the Philosophy of the Social Siences [el Porqué del Desarrollo Insuficiente de la Filosofía de Las Ciencias Sociales] - Caiceo-Escudero, J (FahrenHouse, 2018)
Is intended to demonstrate that the social sciences have not had enough development because Comte legitimized only the methodology of the natural sciences, as the only valid for the social sciences. For his part, Dilthey makes criticism relevant to indicating that social sciences seek to understand the facts, more to explain them as do natural sciences; therefore, must move more in a qualitative paradigm and quantitative not; therefore, proposes to search own for Social Sciences epistemology, as the object of study are men and their relationships which does not have a uniform behavior, as the natural world. The natural sciences seek why phenomena; the social understanding of them. During the 20th century, there were attempts by various philosophers to find an episteme of social sciences for a faster development of the same, without achieving it fully. Hence the crises of the epistemology of social sciences, which have not even a proper expansion. Various epistemological attempts to develop the social sciences hermeneutics of Gadamer, the phenomenology of Husserl, the critique of Habermas philosophy include philosophy of language Wittgenstein and critical rationalism or hypothetical-deductive method of Popper and those who deviate from it, Khun and Lakatos. However, from the ideas of the philosophers mentioned, occurred in the last four decades, a major advance in the development of the social sciences, because there have been studies with emphasis qualitative but quantitative contributions; the natural sciences have also done something similar. At the same time, in the development of the Sciences of education has passed something similar to that described above. © 2018 FahrenHouse. All right reserved.